A lens-shaped, cold-core anticyclonic surface eddy in the northern South China Sea - Qi, Yongfeng; Mao, Huabin; Du, Yan; Li, Xianpeng; Yang, Zhou; Xu, Ke; Yang, Ying; Zhong, Wanxuan; Zhong, Fuchang; Yu, Linghui; Xing, Huanlin (Frontiers in Marine Science, 2022)
Typically, compared with the normal ocean, an anticyclonic eddy has higher sea surface temperature (SST), greater surface mixed-layer depth (MLD), and a bowl-shaped structure under the action of geostrophy. This study is the first to report an abnormal anticyclonic eddy characterised by a lens-shaped structure, cold core, and shallower MLD, which were observed in situ in the northern South China Sea (SCS) in September 2021. The SST at core of the anticyclonic eddy was 0.4°C lower than that in its peripheral region. The MLD at the centre of the eddy was about half of that outside the eddy. Below the surface mixed layer, a lens-shaped structure containing relatively well-mixed water was observed between the two high-gradient layers. Within this lens-shaped structure, the isothermal layers were stretched, but accompanied by water mixing that was about one third of that at the upper and lower bounds of the structure. This eddy originated from a Kuroshio Current intrusion in late October 2020 and died in November 2021, such that its lifespan exceeded 1 year. The shedding of the Kuroshio Loop into the SCS under strong air–sea interactions under continuous sea surface cooling in winter was considered a key mechanism for the generation of the cold core of the eddy. The lens-shaped structure formed below the surface mixed layer and was maintained through geostrophic balance by the subsurface maximum speeds of the Kuroshio Current intrusion (50–100 m), thereby forming a shallower MLD in the eddy centre. The subsurface speed maximum within the eddy was also observed by a shipborne acoustic Doppler current profiler at 10 months after its formation, confirming the hypothesised mechanism. This type of abnormal anticyclonic may be a common phenomenon in the northern SCS and has potential implications for the local biogeochemistry, local heat budget, and regional oceanic models.